Effect of Visual Field Location on Global Motion Perception: A Developmental Study. (July 2020) - Shahin, Yousef M.; Meier, Kimberly; Giaschi, Deborah
Previous work has shown that motion perception in school-age children is similar to that of adults for fast speeds but is immature at slow speeds for stimuli presented in the central visual field. This study examined whether visual field location affects this developmental pattern. We measured left/right and up/down global motion direction discrimination for fast and slow speeds in 7- to 10-year-old children and in adults with stimuli presented to upper, central, or lower visual fields. For left/right direction discrimination, children showed significantly higher (worse) coherence thresholds than adults for slow, but not fast, speeds in the central visual field. In the upper and lower visual fields, children showed significantly higher coherence thresholds than adults for both speeds. For up/down direction discrimination, children showed similar performance to adults for the central visual field. In the upper and lower visual fields, children performed significantly worse than adults; this finding was speed-tuned only for the lower visual field. Thus, children show immature global motion perception in the periphery even when performance in central vision is adult-like. These results enrich our understanding of motion perception development in children with typical vision.